Initial Validation of the Mindful Presence Scale: The Issue of the Construal Level of Scale Items - Lengyel, Attila; Keczeli, Danica; Orosz, Róbert; Bács, Zoltán; Müller, Anetta; Szőke, Szilvia; Bába, Éva Bácsné (Frontiers in Psychology, 2021)
Our research has two main aims. It undertakes the validation of a 6-item trait mindfulness scale called Mindful Presence Scale (MPS) which measures central aspects of mindfulness. For the first time in mindfulness literature, the construal level of scale items is also examined. Four questionnaire-based online studies were conducted. Study 1 drew three samples (nn=391, np=215, nb=235) from the students at the University of Debrecen. It examined the factor structure, reliability and internal consistency of the three differently worded scale versions. The positively worded scale version (MPSp) yielded a stable 2-factor structure and demonstrated the best psychometric properties. Study 2 performed a confirmatory factor analysis on a sample drawn from public employees across the country (ncfa=420).. The two factor solution in study 1 was confirmed. χ2 tests were not significant and fit indices were excellent. There was no significant difference between the high-level construal subscale (Fhlc) and the low-level construal subscale (Fllc) in terms of factorial stability. Participant of study 3 were students who did not take part in study 1. The sample (ninv=250) was tested for measurement invariance across gender. The scaled results supported strong/threshold invariance. Study 4 tested concurrent validity with ten concurrent instruments. A sample of secondary school teachers (ncon=128) was tested by examining Spearman rank order correlations. There was a significant difference in how the Fhlc and Fllc subscales predicted scores of some of the concurrent instruments. Further research is warranted into how the construal level of mindfulness scale items affects recollection of mindful experience. Overall MPSp proved to be a valid short mindfulness measure.